THE APPLICATION OF DEEP LEARNING–BASED ARTIFICIAL INTELLIGENCE IN ENHANCING ENGLISH LISTENING AND SPEAKING SKILLS - Muhammad Eka Zuwanda; Gumarpi Rahis Pasaribu (PT Rahis Cendekia Indonesia, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly influenced educational practices, particularly in English as a Foreign Language (EFL) learning. Deep learning–based AI technologies offer adaptive and interactive learning environments that support the development of communicative language skills. This study aims to examine the application of deep learning–based Artificial Intelligence in enhancing students’ English listening and speaking skills, which are often challenging to develop through conventional instructional methods. This study employed a quasi-experimental research design with a pre-test and post-test control group approach. A total of 30 EFL students participated in the study and were divided into an experimental group (15 students) and a control group (15 students). The experimental group received instruction using deep learning–based AI tools, including automatic speech recognition, adaptive listening materials, and real-time pronunciation feedback, while the control group was taught using traditional methods. Data were collected through listening and speaking tests and analyzed using descriptive statistics and inferential statistical tests. The findings revealed that students in the experimental group showed significantly greater improvement in listening comprehension and speaking performance than those in the control group. The use of AI-based instruction contributed to improved pronunciation accuracy, fluency, and confidence in oral communication. These results indicate that deep learning–based Artificial Intelligence is an effective instructional approach for enhancing English listening and speaking skills and has the potential to support learner-centered and technology-enhanced EFL instruction